Novel knock‐in mouse model for the evaluation of the therapeutic efficacy and toxicity of human podoplanin–targeting agents. Issue 6 (5th April 2021) - Ukaji, Takao; Takemoto, Ai; Shibata, Harumi; Kakino, Mamoru; Takagi, Satoshi; Katayama, Ryohei; Fujita, Naoya
Abstract: Podoplanin is a key molecule for enhancing tumor‐induced platelet aggregation. Podoplanin interacts with CLEC‐2 on platelets via PL atelet Ag gregation–inducing domains (PLAGs). Among our generated antibodies, those targeting the fourth PLAG domain (PLAG4) strongly suppress podoplanin–CLEC‐2 binding and podoplanin‐expressing tumor growth and metastasis. We previously performed a single‐dose toxicity study of PLAG4‐targeting anti‐podoplanin–neutralizing antibodies and found no acute toxicity in cynomolgus monkeys. To confirm the therapeutic efficacy and toxicity of podoplanin‐targeting antibodies, a syngeneic mouse model that enables repeated dose toxicity tests is needed. Replacement of mouse PLAG1‐PLAG4 domains with human homologous domains drastically decreased the platelet‐aggregating activity. Therefore, we searched the critical domain of the platelet‐aggregating activity in mouse podoplanin and found that the mouse PLAG4 domain played a critical role in platelet aggregation, similar to the human PLAG4 domain. Human/mouse chimeric podoplanin, in which a limited region containing mouse PLAG4 was replaced with human homologous region, exhibited a similar platelet‐aggregating activity to wild‐type mouse podoplanin. Thus, we generated knock‐in mice with human/mouse chimeric podoplanin expression ( Pdpn KI/KI mice). Our previously established PLAG4‐targeting antibodies could suppress human/mouse chimeric podoplanin–mediated platelet aggregation and tumor growth in Pdpn KI/KI mice. Repeated treatment of Pdpn KI/KI mice with antibody‐dependent cell‐mediated cytotoxicity activity–possessing PG4D2 antibody did not result in toxicity or changes in hematological and biochemical parameters. Our results suggest that anti‐podoplanin–neutralizing antibodies could be used safely as novel anti‐tumor agents. Our generated Pdpn KI/KI mice are useful for investigating the efficacy and toxicity of human podoplanin–targeting drugs. Abstract : Podoplanin is a key molecule for enhancing tumor‐induced platelet aggregation. Here, we report a knock‐in mouse with human/mouse chimeric podoplanin expression to examine the therapeutic efficacy and toxicity of podoplanin‐targeting agents. Using this knock‐in mouse model, we confirmed that anti‐podoplanin–neutralizing antibodies could be used safely as novel anti‐tumor agents.